2007
DOI: 10.1016/j.otohns.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Undifferentiated Carcinoma of Nasopharyngeal Type with Thallium‐201 and Technetium‐99m MIBI SPECT

Abstract: 201-Tl SPECT and Tc-99m MIBI SPECT are useful for detecting primary UCNT, residual/recurrent disease, and lymph node involvement. This use is particularly valuable after chemoradiotherapy when CT/MRI may be ambiguous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Finally, other researchers suggested that both 201 Tl and 99m Tc-MIBI have the same accuracies in locating primary, recurrent and lymph node involvement and thus could also be valuable. [24] In the study, no relation of the 99m Tc-TF sensitivity with the pathological grade of the tumor was observed, but there was a potential correlation of 99m Tc-TF sensitivity with tumor size. Thus, it appeared to be a trend toward positive uptake with increasing tumor size, which did not reach statistical significance, probably a result of a relatively small number of cases.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, other researchers suggested that both 201 Tl and 99m Tc-MIBI have the same accuracies in locating primary, recurrent and lymph node involvement and thus could also be valuable. [24] In the study, no relation of the 99m Tc-TF sensitivity with the pathological grade of the tumor was observed, but there was a potential correlation of 99m Tc-TF sensitivity with tumor size. Thus, it appeared to be a trend toward positive uptake with increasing tumor size, which did not reach statistical significance, probably a result of a relatively small number of cases.…”
Section: Discussionmentioning
confidence: 67%
“…In the 18 patients studied by Kostakoglu and colleagues, 201 Tl yielded the lowest diagnostic accuracy (72% and 71% at 3 and 6 months post‐treatment). In a later study with a larger sample of 46 NPC patients, Sobic‐Saranovic and colleagues presented differing results demonstrating that the specificity, sensitivity, and accuracy of 201 Tl was actually similar to that of MIBI SPECT imaging (88%, 78%, and 82% versus 86%, 77%, and 81%) 44 . It is unclear, however, if these results can be directly compared to the earlier study performed by Kostakoglu et al as patients in the latter study were subdivided into two groups to receive different imaging modalities (either MIBI SPECT or 201 Tl) rather than both imaging modalities due to the limited availability of tracers and high radiation exposure.…”
Section: Resultsmentioning
confidence: 97%
“… Detection of local recurrence: Optional. Similar to FDG‐PET, TC‐99m MIBI and 201 Tl SPECT detect cancerous tissues based on metabolic activity ( 201 Tl accumulates in cells with high Na‐K‐ATPase activity whereas TC‐99m MIBI concentrates in the mitochondria of tumor tissues) instead of morphological changes 44 . For indeterminate MRI findings, TC‐99m MIBI and 201 Tl SPECT can serve as an adjunctive alternative 43 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations